A comparison of one-dimensional and microscale two-dimensional liquid chromatographic approaches coupled to high resolution mass spectrometry for the analysis of complex samples1. Issue 18 (21st September 2015) - Leonhardt, Juri; Teutenberg, Thorsten; Tuerk, Jochen; Schlüsener, Michael P.; Ternes, Thomas A.; Schmidt, Torsten C.
<x xml:space="preserve">Abstract</x> The interest in two-dimensional liquid chromatography separations is growing every year together with the number of open questions on the benefits.